2014
DOI: 10.1002/ana.24134
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic phospholipase A2 protein as a novel therapeutic target for spinal cord injury

Abstract: ObjectiveThe objective of this study was to investigate whether cytosolic phospholipase A2 (cPLA2), an important isoform of PLA2 that mediates the release of arachidonic acid, plays a role in the pathogenesis of spinal cord injury (SCI).MethodsA combination of molecular, histological, immunohistochemical, and behavioral assessments were used to test whether blocking cPLA2 activation pharmacologically or genetically reduced cell death, protected spinal cord tissue, and improved behavioral recovery after a contu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 58 publications
9
67
0
Order By: Relevance
“…cPLA 2 is an 85kDa protein enzyme that preferentially produces arachidonic acid (AA) by hydrolyzing the sn-2 position of glycerophospholipids [49]. Our lab has previously shown that cPLA 2 activation increased as early as 8 hours and peaked at 7 days post-SCI [22,21]. Activation of cPLA 2 by its activator, ceramide-1-phosphate or A23187, is sufficient to induce neuronal death, whereas cPLA 2 inhibition reduces cell loss in vitro [22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…cPLA 2 is an 85kDa protein enzyme that preferentially produces arachidonic acid (AA) by hydrolyzing the sn-2 position of glycerophospholipids [49]. Our lab has previously shown that cPLA 2 activation increased as early as 8 hours and peaked at 7 days post-SCI [22,21]. Activation of cPLA 2 by its activator, ceramide-1-phosphate or A23187, is sufficient to induce neuronal death, whereas cPLA 2 inhibition reduces cell loss in vitro [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our lab has previously shown that cPLA 2 activation increased as early as 8 hours and peaked at 7 days post-SCI [22,21]. Activation of cPLA 2 by its activator, ceramide-1-phosphate or A23187, is sufficient to induce neuronal death, whereas cPLA 2 inhibition reduces cell loss in vitro [22]. Following acute SCI, cPLA 2 inhibition reduces inflammation, cell death, tissue damage and improves functional recovery [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations